2010
DOI: 10.1088/0256-307x/27/9/090301
|View full text |Cite
|
Sign up to set email alerts
|

A New Quantum Key Distribution Scheme Based on Frequency and Time Coding

Abstract: A new scheme of quantum key distribution (QKD) using frequency and time coding is proposed, in which the security is based on the frequency-time uncertainty relation. In this scheme, the binary information sequence is encoded randomly on either the central frequency or the time delay of the optical pulse at the sender. The central frequency of the single photon pulse is set as 1 ω for bit "0" and set as 2 ω for bit "1" when frequency coding is selected. While, the single photon pulse is not delayed for bit "0"… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Polarizing mode dispersion is one of incoherent temporal broadening [44][45][46]. Due to a coupling between the polarization and frequency degree of freedom, if the polarization is not measured, the single photon state becomes mixed in frequency [47]. Thus, the error correction protocol that will be presented in Sec.…”
Section: Sources Of Time-frequency Noisementioning
confidence: 99%
“…Polarizing mode dispersion is one of incoherent temporal broadening [44][45][46]. Due to a coupling between the polarization and frequency degree of freedom, if the polarization is not measured, the single photon state becomes mixed in frequency [47]. Thus, the error correction protocol that will be presented in Sec.…”
Section: Sources Of Time-frequency Noisementioning
confidence: 99%
“…In their work, Pietro et al (2023) [37] compared the performance of QKD with other encryption techniques in UWOC. They showed that QKD outperforms other techniques in terms of security, key generation rate, and resistance to eavesdropping.…”
Section: Comparison With Other Encryption Techniquesmentioning
confidence: 99%
“…Since then, many QKD schemes have been proposed based on different coding techniques. Examples include phase coding [5], frequency coding [6], and time-coding [7].…”
Section: Introductionmentioning
confidence: 99%